Impact of environmental pollution on the ocular surface of Sjögren’s syndrome patients - Galperín,Gustavo (2018)
ABSTRACT Purpose: To evaluate the effect of air pollution on the ocular surface of patients with Sjögren’s syndrome. Methods: We investigated the ocular surfaces of thirty patients with Sjögren’s syndrome and thirty healthy volunteers (control group) living in the Metropolitan Area of Buenos Aires. We used nitrogen dioxide as an indicator of exposure to air pollution. An ocular symptoms questionnaire was answered by all subjects, who also underwent a complete ocular surface ophthalmic examination-including an Ocular Surface Disease Index questionnaire, biomicroscopy, tear breakup time, Schirmer 1 test, corneal and conjunctival vital staining with fluorescein and lissamine green, tear lysozyme concentration, and impression cytology. Results: In almost all ocular surface test findings, we found a positive and significant correlation between higher levels of exposure to air pollution and higher levels of ocular surface damage in both the control group and Sjögren’s syndrome patients. In Sjögren’s syndrome patients, the Ocular Surface Disease Index questionnaire, tear breakup time, vital staining and impression cytology showed a significant correlation between high levels of air pollution and ocular surface disease. In the control group, the Ocular Surface Disease Index questionnaire, tear breakup time, and impression cytology showed a significant correlation between high levels of air pollution and ocular surface disease. Conclusions: Here we demonstrated that in patients with dry eye syndrome associated with Sjögren, abnormalities of the ocular surface and eye irritation related to air pollution are more severe than those in the control group. We believe that measuring air quality should be not only an integral part of the evaluation of ocular surface disease but also a therapeutic consideration.